2020
DOI: 10.1101/2020.02.06.937151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual mental imagery engages the left fusiform gyrus, but not the early visual cortex: a meta-analysis of neuroimaging evidence

Abstract: The neural bases of visual mental imagery (VMI) are the object of intense debate. Their identification is central to define the brain substrates our conscious experience and can be clinically important to reveal consciousness in non-communicating patients or to alleviate posttraumatic stress disorder. The dominant model of VMI stipulates a functional and anatomical equivalence between visual mental imagery and visual perception. In patients with acquired brain damage, the model predicts a systematic co-occurre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 144 publications
(258 reference statements)
0
4
0
Order By: Relevance
“…But we might worry that they fail to pinpoint specific failings in this area. Spagna et al (2021) approach the V1 controversy from a different angle. They are concerned to highlight observations of brain-damaged patients in clinical contexts that are "sharply discordant" (p. 202) with the experimental results yielded from the study of healthy, neurotypical subjects, and which supposedly show the necessity of V1 for imagery.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…But we might worry that they fail to pinpoint specific failings in this area. Spagna et al (2021) approach the V1 controversy from a different angle. They are concerned to highlight observations of brain-damaged patients in clinical contexts that are "sharply discordant" (p. 202) with the experimental results yielded from the study of healthy, neurotypical subjects, and which supposedly show the necessity of V1 for imagery.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Two kinds of vision/imagery double dissociations found in the clinical literature bear on this discussion. Reflection on them can be used to flesh out the above claims by Spagna et al (2021).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Individuals still report being able to create mental images despite near-complete bilateral lesions to primary visual cortex, suggesting that the primary visual cortex is not necessary for visual mental imagery (Bridge et al, 2012;Chatterjee & Southwood, 1995;de Gelder et al, 2015;Zago et al, 2010). Further, a systematic review of the neural correlates of visual mental imagery by Spagna et al (2020) found that the left fusiform gyrus, a high-level region within the visual ventral stream, was the only region reliably involved during mental imagery across studies (although the authors do not exclude the involvement of more anterior regions of the temporal lobe given the known difficulty in imaging these regions). These findings are entirely in line with the predictions of our model: while primary sensory cortices can be involved in mental imagery, the only essential component of the experience is the internal generation of a non-veridical stimulus representation, which in our model occurs at the hierarchical apex, corresponding, for instance, to late in the visual ventral stream.…”
Section: Distinguishing Imagined and Veridical Perceptsmentioning
confidence: 99%
“…Future studies may therefore seek to expand the approach here to alternate models of sensory processing, although our model is still capable at emulating findings on how imagined and veridical information is distributed in real human brains (e.g. Lee et al, 2012;Spagna et al, 2020;VanRullen & Reddy, 2019).…”
Section: Neural Plausibility and Opposing Explanationsmentioning
confidence: 99%